Challenges Facing Nurses toward Providing Care for Patients at Intensive Care Units during the Pandemic of Corona Virus Disease - Jameel Yousif Khalaf, Serwan Jafar Bakey (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nurses constitute the majority of healthcare practitioners, have been fighting the COVID-19 outbreak on the front lines. Nurses could face several challenges during delivering care for patients at ICUs especially at the time of pandemic of COVID -19, including workload and shortage, psychological load, availability of resources, responsibilities, and role conflict. Aims of the study: To what extent is there a significant relationship between challenge that facing nursing care at intensive care unit during the pandemic of corona virus ? Methodology: A descriptive study design was conducted on ICU nurses at Baquba teaching hospital for the period October 15th, 2021, to March 25th, 2022. A non-probability (Purposive) sample was selected of 35 nurses who work at Baquba teaching hospital. The data was collected using a previously prepared questionnaire and official agreement to use the study questionnaire was obtained from the original author. Descriptive statistics (frequencies, percentages, mean, and standard deviation) and inferential statistics (person correlation) were used in the data analysis. Results: Results showed that nurses who work at ICU during the pandemic of COVID -19 were faced several challenges to deliver care for patients, including shortage of nurses in the presence of large number of patients, lack of appropriate offices for nurses, stressful work environment, sense responsibilities for some critical cases, and lack of support from superiors. Conclusion: The study concluded that nurses who work at ICU during the pandemic of COVID -19 were faced several challenges to deliver care for patients, including shortage and workload, psychological load, taking responsibilities, and role conflict challenges.